Research design and methods : a process approach - Bordens, Kenneth S.; Abbott, Bruce B. (New York : McGraw-Hill Education, 2022)
"We take students through research process, from getting and developing a research idea, to designing and conducting a study, through analyzing and reporting data. Our goals continue to be to present students with information on the research process in a lively and engaging way and to highlight the numerous decisions they must make when designing and conducting research. We also continue to stress how their early decisions in the process affect how data are collected, analyzed, and interpreted later in the research process. Additionally, we have continued the emphasis on the importance of ethical conduct, both in the treatment of research subjects and in the conduct of research and reporting research results. In this edition we have rewritten material to improve clarity and organization, provided new examples, updated the material in numerous areas to reflect changes in current requirements and practice, and added more than 70 new references"--
Includes bibliographical references and index.
Keywords: Psychology -- Research; Psychology -- Research -- Methodology